2019
DOI: 10.1038/s41539-019-0047-z
|View full text |Cite
|
Sign up to set email alerts
|

Does splitting sleep improve long-term memory in chronically sleep deprived adolescents?

Abstract: Sleep aids the encoding and consolidation of declarative memories, but many adolescents do not obtain the recommended amount of sleep each night. After a normal night of sleep, there is abundant evidence that a daytime nap enhances the consolidation of material learned before sleep and also improves the encoding of new information upon waking. However, it remains unclear how learning is affected when sleep is split between nocturnal and daytime nap periods during a typical school week of restricted sleep. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 50 publications
(73 reference statements)
1
31
0
1
Order By: Relevance
“…Total or partial sleep restriction can compromise new memory formation [ 43–45 ] (although see [ 46 ]). A daytime nap has been shown to be beneficial—both in the context of sleep restriction [ 11 ], as well as following a normal night of sleep [ 10 ], reinforcing the idea that sleep may not just necessary for normative cognitive performance, but may also boost memory beyond that of habitual, nocturnal sleep [ 47 ]. In this study, we showed that participants who had a 90-minute afternoon nap in addition to a habitual, nonrestricted night of sleep encoded 21% more word pairs on average than those who stayed awake during the nap period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total or partial sleep restriction can compromise new memory formation [ 43–45 ] (although see [ 46 ]). A daytime nap has been shown to be beneficial—both in the context of sleep restriction [ 11 ], as well as following a normal night of sleep [ 10 ], reinforcing the idea that sleep may not just necessary for normative cognitive performance, but may also boost memory beyond that of habitual, nocturnal sleep [ 47 ]. In this study, we showed that participants who had a 90-minute afternoon nap in addition to a habitual, nonrestricted night of sleep encoded 21% more word pairs on average than those who stayed awake during the nap period.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that a mid-afternoon nap facilitates picture encoding [ 11 ] and found behavioral evidence that suggested enhanced hippocampal function as a plausible mechanism [ 12 ]. Memory encoding following sleep may occur as a result of (1) improvement in attentiveness to the learned material [ 13 ], (2) active systems consolidation, resulting from the transfer of labile memories in the hippocampus to neocortex for long-term storage, thus freeing up hippocampal encoding capacity for new learning [ 14 ], or (3) synaptic downscaling [ 15 ] whereby synaptic connections potentiated during wakefulness are downscaled to avoid saturation and to increase the signal-to-noise ratio for salient information.…”
Section: Introductionmentioning
confidence: 99%
“…Memory was tested after one night of recovery sleep on day R2 2 (20:30) via two-alternative forced choice questions followed by confidence ratings (certain, somewhat certain and guess). Consistent with prior work using this task (Cousins, et al, 2019b, 2019c, 2019d), our analysis focussed on certain responses that were corrected for response bias (correct-incorrect). We conducted a 2×2×2 mixed ANOVA to examine the effects of schedule (split/continuous), duration (6.5h/8h), and time (morning/afternoon) on certain memory (correct−incorrect).…”
Section: Resultsmentioning
confidence: 99%
“…Addressing this, the current study replicated our prior experiment with two additional groups of adolescents (Table 1) that were afforded the minimum recommended for this age group of 8h sleep opportunity each day (8h-split and 8h-continuous), then compared their performance with groups from the prior study (6.5h-split and 6.5h-continuous) (Cousins et al, 2019b). The effect of these schedules on sleep physiology and declarative memory (picture encoding and factual knowledge task) was investigated across two simulated school weeks (Fig.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation